Settler Colonialism in the Digital Age: Clash of Clans, Territoriality, and the Erasure of the Native - Euteneuer, Jacob (Open Library of Humanities, 2018)
In the past ten years, two seemingly unconnected fields of study have risen to prominence. Patrick Wolfe’s 2006 theorization of settler colonialism called for the development of a distinct set of literature and analytical tools to analyze the relationship between indigenous peoples and occupying settlers. Meanwhile, Ian Bogost’s 2007 elaboration of the notion of procedural rhetoric provided a theoretical framework to approach the critical analysis of the ideology modeled by a game’s rules and design. While each of these theories have proliferated and prospered within their disciplines, this article seeks to bring the two fields together in order to establish a critical framework that can be used to highlight the presence of settler colonialism in popular mobile videogames, in particular Supercell’s 2012 mobile game Clash of Clans. Within this framework, the essay analyzes how the game engages in a system of play driven by its focus on improvement, progression, and expansion, which ends up operating under the same principles settler colonialism has used to justify the expansion of settler-states and the eradication of indigenous populations. Through an examination of the game’s economy, enemies, maps, and music, the essay connects the game’s systems of play to the embedded nature of settler colonialism in the videogame industry—particularly the mobile or casual scene—and contemporary life in settler-states. The ultimate goal is to explain how social meaning is derived from these types of games and what that means for both players and creators in terms of developing new, progressive opportunities for play.
Number: 1
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé